Storytelling in opera and musical theater - Penner, Nina (Musical meaning and interpretation., 2020)
"Storytelling in Opera and Musical Theater is the first systematic exploration of how sung forms of drama tell stories. Through examples from opera's origins to contemporary musicals, Nina Penner examines the roles of character-narrators and how they differ from those in literary and cinematic works, how music can orient spectators to characters' points of view, how being privy to characters' inner thoughts and feelings may evoke feelings of sympathy or empathy, and how performers' choices affect not only who is telling the story but what story is being told. Unique about Penner's approach is her engagement with current work in analytic philosophy. Her study reveals not only the resources this philosophical tradition can bring to musicology but those which musicology can bring to philosophy, challenging and refining accounts of narrative, point of view, and the work-performance relationship within both disciplines. She also considers practical problems singers and directors confront on a daily basis, such as what to do about Wagner's Jewish caricatures and the racism of Orientalist operas. More generally, Penner reflects on how centuries-old works remain meaningful to contemporary audiences and have the power to attract new, more diverse audiences to opera and musical theater. By exploring how practitioners past and present have addressed these issues, she offers suggestions for how opera and musical theater can continue to entertain and enrich the lives of 21st century audiences"--